Towards a rhetoric of cross-cultural identity - Sell, Jonathan P.A. (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2008)
This paper explores the involvement of metaphor and allusion in the discursive construction of cross-cultural identity. Cross-cultural identity is regarded as a narrative; as such it is liable to rhetorical analysis and dependent on rhetorical processes for its construction and assimilation. Metaphor is claimed to serve both as an analogy for the act of cross-cultural communication and cognition and as a fundamental enabling means of that communication and cognition. Allusion is, likewise, claimed to serve as another analogy on the semiotic and mimetic levels, this time for the experiential condition of the cross-cultural subject, while more pragmatically, it acts as a means for negotiating a palatable identity in a given host community. In conclusion, it is suggested that rhetorical analysis may provide a fruitful tool for affirming the possibility of cross-cultural communication and for understanding how it may actually work.